Risk selection into supplemental private health insurance in China - Yawen Jiang; Weiyi Ni (Health Economics Review, 2019)
Background: Information on risk selection is important for the regulation and development of supplemental private health insurance (PHI). The research on risk selection into supplemental PHI has been documented in several developed countries where the regulation of the PHI markets was relatively mature. However, evidence on this important aspect of the supplemental PHI market in China is still absent in the literature. The private insurers in China were not prohibited from discrimination against pre-existing conditions and did not guarantee ongoing enrolment. Therefore, the direction and degree of risk selection could not be inferred using the evidence from the other countries. To provide evidence on risk selection into supplemental PHI in China, we conducted a crosssectional analysis using data from the 2015 wave of China Health and Retirement Longitudinal Study (CHARLS). Results: Using probit models, we found that individuals having better self-reported general health were more likely to enrol in PHI in China, suggesting advantageous selection. This result was confirmed by an alternative analysis using an instrumental variable. We also adjusted the realized occurrence of hospitalization by excluding potential moral hazard effect and showed that the adjusted hospitalization risk was negatively associated with PHI enrolment, which also indicated advantageous selection. Conclusions: The findings suggested potential over-insurance of healthier individuals or under-insurance of less healthy individuals. The regulation of the PHI market in China should aim to address the inefficiency. The current study could also contribute to the information base for policymakers in countries where the PHI markets similarly lack strong regulation.
Keywords: 330; Private; Health insurance; Risk; Selection; Advantageous